2010
DOI: 10.1038/sj.bjc.6605737
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and outcome in advanced colorectal cancer patients with synchronous vs metachronous metastases

Abstract: Background:Synchronous metastases of colorectal cancer (CRC) are considered to be of worse prognostic value compared with metachronous metastases, but only few and conflicting data have been reported on this issue.Methods:We retrospectively investigated patient demographics, primary tumour characteristics and overall survival (OS) in 550 advanced CRC patients with metachronous vs synchronous metastases, who participated in the phase III CAIRO study. For this purpose only patients with a prior resection of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 27 publications
5
100
1
7
Order By: Relevance
“…By contrast, according to the subgroup analysis of the CAIRO study described above, metachronous metastases originated from smaller primary CRC, and smaller T and N numbers than synchronous metastases. They also described that extrahepatic organs were more frequently involved in metachronous metastases [19]. These results are in accordance with our observation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…By contrast, according to the subgroup analysis of the CAIRO study described above, metachronous metastases originated from smaller primary CRC, and smaller T and N numbers than synchronous metastases. They also described that extrahepatic organs were more frequently involved in metachronous metastases [19]. These results are in accordance with our observation.…”
Section: Discussionsupporting
confidence: 83%
“…One plausible reason is that previous chemotherapy, most frequent in the FOLFOX group (71%), had a good chance to confer chemoresistance to tumor cells, therefore multiple micrometastases were more likely to grow into clinically overt metastases heterochronically. In a subgroup analysis of the CAIRO study, a randomized phase III trial of capecitabine, irinotecan, and oxaliplatin for unresectable CRC, the authors suggested this possibility as an explanation for the lower response rate in CRC patients with metachronous metastases compared to those with synchronous metastases [19]. However, in our series, both the 2 chemotherapy-naïve patients who underwent FOLFOX after curative resection of metachronous metastases developed metastases again (data not shown); thus, distinct scenarios must be considered.…”
Section: Discussionmentioning
confidence: 99%
“…According to a definition by Mekenkamp et al, 36 18 DM were synchronous (onset within 6 months after primary diagnosis of Figure 1) was significantly more frequently seen in LN than in PT and DM, considering both the number of included patients (p = 0.0248 and p = 0.0082) or the number of investigated tumor samples (p = 0.0183 and p = 0.0005). The distribution of mtMSI in the three different loci is displayed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Although, by definition, all metastases are synchronous (occult or detectable at diagnosis), most definitions include detection at or before diagnosis or surgery of the primary tumour [13], whilst some also include metastases detected up to 3 [14,15], 4 [16] or 6 months [17,18] following diagnosis.…”
Section: Definition and Prognosis Of Synchronous Lmmentioning
confidence: 99%